A novel conserved mechanism for plant NLR protein pairs: the ‘integrated decoy’ hypothesis - cesari, Stella; Bernoux, Maud; Moncuquet, Philippe; Kroj, Thomas; Dodds, Peter N. (Frontiers in Plant Science, 2014)
Plant immunity is often triggered by the specific recognition of pathogen effectors by intracellular nucleotide-binding, leucine-rich repeat (NLR) receptors. Plant NLRs contain an N-terminal signaling domain that is mostly represented by either a Toll-interleukin1 receptor (TIR) domain or a coiled coil (CC) domain. In many cases, single NLR proteins are sufficient for both effector recognition and signaling activation. However, many paired NLRs have now been identified where both proteins are required to confer resistance to pathogens. Recent detailed studies on the Arabidopsis thaliana TIR-NLR pair RRS1 and RPS4 and on the rice CC-NLR pair RGA4 and RGA5 have revealed for the first time how such protein pairs function together. In both cases, the paired partners interact physically to form a hetero-complex receptor in which each partner plays distinct roles in effector recognition or signaling activation, highlighting a conserved mode of action of NLR pairs across both monocotyledonous and dicotyledonous plants. We also discuss a new ‘integrated decoy’ effector recognition model to describe these receptor complexes that may be common to many other plant NLR pairs.